Sulfhydrylated albumin mitigates Acetaminophen-induced liver injury by restoring the integrated H2S-albumin thiol antioxidant network - Xin Wang; Yang Sui; Rui Jiang; Yijun Xu; Mika Suda; Jie Cheng; Yingyu Zhang; Zhuheng Shi; Jianglin Fan; Jian Yao (Redox Biology)
Acetaminophen (APAP) overdose is the leading cause of acute liver failure and a major global health issue. APAP hepatotoxicity is primarily driven by oxidative stress resulting from the depletion of hepatic glutathione (GSH). Given that hydrogen sulfide (H2S) and albumin are crucial components of the thiol antioxidant system, we hypothesized they play a critical role in the body's defense against APAP-induced liver injury (AILI). This study aimed to test this hypothesis and explore novel therapeutic approach. Administration of APAP to mice induced significant hepatic damage, associated with marked local and systemic oxidative stress, evidenced by elevated serum transaminases and oxidative injury markers. Furthermore, APAP exposure disrupted the hepatic H2S-generating system, leading to reduced expression of H2S-synthesizing enzymes and decreased levels of H2S and protein persulfidation (-SSH) in both liver and serum. Pharmacological inhibition of endogenous H2S production dramatically exacerbated APAP hepatotoxicity and mortality. Conversely, supplementation with a modified persulfide-rich albumin (Alb-SSH) significantly alleviated hepatocyte injury. These findings were similarly observed in cultured hepatocytes. Mechanistic analysis revealed that Alb-SSH increased H2S levels by releasing H2S and restoring H2S-synthesizing enzymes. It improved both hepatic and systemic oxidative status and rebalanced the intra- and extracellular GSH/GSSG ratio. At the molecular level, Alb-SSH directly scavenged reactive oxygen species and integrated with the GSH/GSSG system via thiol-disulfide exchange reactions. Collectively, our study establishes H2S and Alb-SSH as integral components of a coordinated thiol antioxidant network that counteracts AILI. Supplementation with Alb-SSH represents a promising therapeutic strategy for AILI and other oxidative stress-associated diseases.